2016
DOI: 10.1177/1541931213601134
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic Usability Evaluation of Wearable Mental State Monitoring Sensors for Healthcare Environments

Abstract: In recent years, there has been tremendous growth in both the number and diversity of wearable sensors, including sensors for monitoring mental state. Understanding physiological metrics such as fatigue and stress is an important aspect of human factors research, yet collecting and analyzing these measures can be resource intensive. This paper explores the usability and applicability of four off-the-shelf wearable sensors (Emotiv Epoc, Melon Headband, Spire Stone, and Muse™ Headband) for applied healthcare res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Being able to link those signals back to specific emotions, among a possible myriad of other movements and states, may simply have been too complex. Although some basis for the wearable device was provided by the company [87,88], these papers did not constitute an actual validation of the algorithms of the device. Unfortunately, we were unable to obtain the algorithms and, as such, the scientific contribution of our study is more utilitarian than mechanistic.…”
Section: Potential Device Effectivenessmentioning
confidence: 99%
“…Being able to link those signals back to specific emotions, among a possible myriad of other movements and states, may simply have been too complex. Although some basis for the wearable device was provided by the company [87,88], these papers did not constitute an actual validation of the algorithms of the device. Unfortunately, we were unable to obtain the algorithms and, as such, the scientific contribution of our study is more utilitarian than mechanistic.…”
Section: Potential Device Effectivenessmentioning
confidence: 99%
“…These studies found that, while mobile sensors are not as accurate as a wired and full-scale EEG device, they can be used in noncritical applications. Some recent studies into the benefits of mobile EEG sensors on different domains have demonstrated an acceptable reliability (Leape, Fong, & Ratwani, 2016;Lushin & others, 2016;Wu, Wei, & Tudor, 2017;F. Zhang et al, 2017).…”
Section: Towards the Use Of Mobile Eeg Sensors For Real World Applicamentioning
confidence: 99%
“…Muse has been validated as a device for conducting Event-Related Potential (ERP) research [24]. This device has been compared with other wearable sensors resulting in high performance in the fields of ease of integration and applied usability [25]. In addition, many other studies have used Muse for several purposes, including brain wave activity detection during training [26], enjoyment evaluation [27], accelerometer measurement of head movement during surgery [28], and concentration and stress measurement during surgery [29].…”
Section: Introductionmentioning
confidence: 99%